Renal nerve ablation reduces blood pressure in resistant hypertension: Long‐term clinical outcomes in a single‐center experience. Issue 4 (25th March 2018) - Denegri, Andrea; Naduvathumuriyil, Tino; Lüscher, Thomas Felix; Sudano, Isabella
Abstract : Approximately 10% of patients with hypertension have resistant hypertension, even if adequate pharmacological therapy is established. In this regard, renal nerve ablation (RNA) could represent a valid alternative treatment option. In a retrospective analysis with a follow‐up of 6, 12, and 24 months, the authors investigated the efficacy and safety of catheter‐based renal artery ablation in 57 patients undergoing RNA with multiple renal nerve ablation in both renal arteries. In addition to medical antihypertensive therapy (4.2 ± 1.4 drugs per patient), RNA using three different ablation systems was performed in patients with confirmed resistant hypertension (systolic blood pressure >140 mm Hg in spite of three drugs including a diuretic). The primary end point was the change in office ambulatory systolic blood pressure from baseline to 6, 12, and 24 months of follow‐up after RNA. The primary safety end point was the change in plasma creatinine levels after 12 and 24 months compared with baseline. The mean office systolic blood pressure at baseline was 167.6 ± 22.4 and after 6, 12, and 24 months averaged 143.5 ± 21.1 ( P  <   .05), 141.1 ± 21.1 ( P  <   .05), and 139.4 ± 19.6 mm Hg ( P  <   .05) respectively, with an average of 15.1 ± 5.3 nerve ablations performed. No significant changes in plasma creatinine levels were observed at 12 months ( P  =   .421) and at 24 months ( P  =   .217). There were no complications after RNA nor any relevant adverse vascular, renal, or cardiovascular events observed except in one patient in whom a covered stent had to be placed at the femoral puncture site. In this study, in all patients with resistant hypertension, RNA, if performed adequately in the number of ablations and energy delivery, is an efficient and safe treatment option to lower office and 24‐hour blood pressure. Whether these blood pressure–lowering effects will lead to a reduction of cardiovascular morbidity and mortality will require further studies.